Novel Approaches in Sensorless Induction Motor Drive for Industrial Applications - et. al., Shrinivas P. Ganjewar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In recent years, the use of sensorless induction motor drives is increasing in the fields ranging from industrial to household electrical applications. The major advantage of sensorless motor control technique include lower cost, high reliability, reduced hardware difficulty, noise free operation, and less maintenance requirements. To meet the current requirements of industrial applications more advanced sensorless control techniques are needed. For sensorless motor drives at low and zero-speed operation, inverter nonlinearities and motor parameter variation have significant impact on the stability of control system. Meanwhile, high observer’s bandwidth is required in high-speed region. This paper introduces the state of art of recent progress in sensorless AC motor drives like Improved Q-MRAS, Virtual Current Sensor and Genetic Algorithm etc.